A Population Study of Relative Age Effects on National Tests in Reading Literacy - Vestheim, Ole Petter; Husby, Magne; Aune, Tore Kristian; Bjerkeset, Ottar; Dalen, Terje (Frontiers in Psychology, 2019)
We examined relative age effects (RAE) in national test results in reading literacy in Norway in 2013, in Grades 5, 8, and 9 students (n=173,421) to estimate how month of birth is associated with mean scores and different achievement levels. The results confirm that there is an approximately linear decrease in test scores across months of birth for all grades and both genders. Consequently, students born early in the year are more likely to end up at higher achievement levels than students born later in the year. Further, we found increasing gap in test scores between girls and boys from grade 5 to 8 and 9. We suggest both maturity and motivational reasons for these differences.